Ablation dynamics in coiled wire-array Z-pinches - Hall,GN; Lebedev,SV; Suzuki,Vidal F; Swadling,G; Chittenden,JP; Bland,SN; Harvey,Thompson A; Knapp,PF; Blesener,IC; McBride,RD; Chalenski,DA; Blesener,KS; et al. (Physics of Plasmas, 2013)
Experiments to study the ablation dynamics of coiled wire arrays were performed on the MAGPIEgenerator (1 MA, 240 ns) at Imperial College, and on the COBRA generator at Cornell University’sLaboratory of Plasma Studies (1 MA, 100 ns). The MAGPIE generator was used to drive coiled wiresin an inverse array configuration to study the distribution of ablated plasma. Using interferometry tostudy the plasma distribution during the ablation phase, absolute quantitative measurements ofelectron line density demonstrated very high density contrasts between coiled ablation streams andinter-stream regions many millimetres from the wire. The measured density contrasts for a coiledarray were many times greater than that observed for a conventional array with straight wires,indicating that a much greater axial modulation of the ablated plasma may be responsible for theunique implosion dynamics of coiled arrays. Experiments on the COBRA generator were used tostudy the complex redirection of plasma around a coiled wire that gives rise to the ablation structureexhibited by coiled arrays. Observations of this complex 3D plasma structure were used to validatethe current model of coiled array ablation dynamics [Hall et al., Phys. Rev. Lett. 100, 065003(2008)], demonstrating irrefutably that plasma flow from the wires behaves as predicted. Coiled wireswere observed to ablate and implode in the same manner on both machines, indicating that currentrise time should not be an issue for the scaling of coiled arrays to larger machines with fast currentrise times.